Interleukin-35 Is Involved in Angiogenesis/Bone Remodeling Coupling Through T Helper 17/Interleukin-17 Axis - Zhang, Hui; Li, Yuxuan; Yuan, Lin; Yao, Lutian; Yang, Jie; Xia, Liping; Shen, Hui; Lu, Jing (Frontiers in Endocrinology, 2021)
Objective Osteoporosis is a common metabolic bone disease mainly involving bone remodeling and blood vessels. The current study aimed to explore the suppressive role of interleukin (IL)-35 in nuclear factor kappa-B ligand receptor activator (RANKL) and macrophage colony stimulating factor (M-CSF)-induced osteoclastogenesis and angiogenesis in osteoclasts. Methods Osteoclasts differentiation were induced by incubation of mouse leukemic monocyte/macrophage cell line RAW264.7 cells in the presence of RANKL and M-CSF and was assessed with tartrate-resistant acid phosphatase (TRAP) staining assay. The viability and apoptosis of RAW264.7 was measured using CCK-8 assay and flow cytometry, respectively. The expression of angiogenic genes and proteins were measured using RT-PCR, Western blots and ELISA. The inhibition of Th17/IL-17 axis was examined using plumbagin, which was demonstrated as an IL-17A related signaling pathway inhibitor. Results IL-35 inhibited the viability of RAW264.7 cells and promoted the apoptosis of RAW264.7 cells in a dose-dependent manner. Furthermore, IL-35 dose-dependently suppressed the expression of angiogenic markers including VEGF and its receptor. The suppressive effect of IL-35 was confirmed through the activation of Th17/IL-17 axis. Conclusions We demonstrated for the first time the immuno-suppressive function of IL-35 on RANKL and M-CSF-induced osteoclastogenesis and angiogenesis through Th17/IL-17 axis. Therapeutic approach involving augmentation of IL-35 regulatory response may serve as a novel treatment option for osteoporosis, especially by suppressing bone resorption and angiogenesis.